2017
DOI: 10.1159/000484920
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Curcumin Protects Kidney Tubules Against Renal Ischemia-Reperfusion Injury (RIRI) by Modulating Nitric Oxide (NO) Signaling Pathway

Abstract: Background/Aims: To explore the protective effect of curcumin on renal ischemia-reperfusion injury (RIRI) in rats, and its influence on nephridial tissue’s NO and cGMP levels as well as downstream signaling pathway, to elucidate the possible mechanism of curcumin on RIRI. Methods: 36 Sprague Dawley rats (SD rats) were randomly divided into Sham group, Model group, curcumin (CUR +) Model group, 12 rats per group. They were all given RIRI model preparation by unilateral artery occlusion method. All groups’ β2-MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…The detected decrease in serum NO level in AP group treated with curcumin in our study may be due to inhibition of induction of iNOS, which resulted in decrease in NO level, which is in agreement with Liu et al (2017) who have demonstrated that the iNOS/NO signaling pathway was suppressed with curcumin treatment indicating that the preventive effect of curcumin could be mediated by its ability to suppress the transcription of iNOS and attenuate the downstream signaling pathway of iNOS/NO. iNOS rather than eNOS is the major NOS that is responsible for the dramatic increase in the production of NO and activation of the signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The detected decrease in serum NO level in AP group treated with curcumin in our study may be due to inhibition of induction of iNOS, which resulted in decrease in NO level, which is in agreement with Liu et al (2017) who have demonstrated that the iNOS/NO signaling pathway was suppressed with curcumin treatment indicating that the preventive effect of curcumin could be mediated by its ability to suppress the transcription of iNOS and attenuate the downstream signaling pathway of iNOS/NO. iNOS rather than eNOS is the major NOS that is responsible for the dramatic increase in the production of NO and activation of the signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…However, curcumin, apocynin and diphenyliodonium have antioxidant functions that inhibit nitric oxide synthesis, xanthine oxidase, cytochrome P450 reductase, and mitochondrial enzymes. For these reasons, definitively attributing the neutralization of ischemia-reperfusion injury by apocynin and diphenyliodonium to NOX enzyme inhibition is difficult [62-67]. …”
Section: Mechanisms Of Nadph Oxidase Induction Of Oxidative Stress Inmentioning
confidence: 99%
“…Unfortunately, although reperfusion restores blood flow to infarcted kidney tissues, the reperfusion itself also induces additional damage to the kidney tissue, which is referred to as ischemia-reperfusion (I/R) injury [2, 3]. In spite of the extensive research that has been carried out over the past six decades in the field of renal IR injury [4, 5], the pathogenesis of reperfusion-mediated kidney damage is poorly understood [6]. …”
Section: Introductionmentioning
confidence: 99%